Jenis Tumbuhan Obat yang Dimanfaatkan Untuk Pasca Melahirkan Oleh Etnis Melayu Di Tanjung Pura Kabupaten Langkat, Sumatera Utara - Bela Yustika; Jamilah Nasution; Riyanto Riyanto (Universitas Medan Area, 2022)
Medicinal plants come from natural ingredients and are passed down from generation to generation. Ethnic Malay is one of the tribes who use plants for postnatal treatment. This study aims to identify the types of plants found in postpartum treatment by the Malay tribe in Tanjunpra, Langkat Regency, North Sumatra. The method used is descriptive qualitative and quantitative with emic and ethical approaches. In collecting sample data, we used the interview method and the selection of informants by means of